PERANAN WIRAUSAHA BUDIDAYA JAMUR TIRAM SEBAGAI PEMBERDAYAAN REMAJA (Studi Kasus di Kecamatan Gisting Kabupaten Tanggamus) - Permana, Fitra; Wirawan, Bintang (SOCIOLOGIE, 2013)
This study aims to describe the process of oyster mushroom cultivation, explains the constraints and strategies in the cultivation of oyster mushroom, and explains the role of entrepreneurship in the oyster mushroom cultivation in District Gisting adolescents empowerment Tanggamus. This study uses qualitative methods. Collecting data using in-depth interview techniques. The results showed that. First, the process of oyster mushroom cultivation in the District Gisting starts from obtaining the oyster mushroom cultivation, namely: through friends, books, the internet, and training. Motivation oyster mushroom cultivation: business opportunities, skill requirements are not so high, the process relatively easy maintenance, not knowing the season, delicious food alternatives, healthy and highly nutritious, and does not cause environmental pollution. Second, internal constraints include the capital and the (mushroom) is less extensive. Strategies in the internal constraints are borrowing from the bank, modify the shelves in the mushroom house mushroom production further external constraints include the supply of raw materials and the scarcity of seeds. Strategies in the external constraints are stockpiling of raw materials, bought seeds from Purwokerto, Central Java and start doing experiment in developing seeds Thirdly, entrepreneurial empowerment conducted by the oyster mushroom cultivation with enablement in oyster mushroom cultivation and positive motivation to the business world, adolescents are expected to be an independent entrepreneur.Keywords: Roles, entrepreneurship, oyster mushroom cultivation, empowerment, adolescents